Biomimetic spray coating for fruit preservation based on UiO-1 67 metal–organic framework nanozyme - Li, Jie; Wang, Donglin; Liu, Yuhang (Frontiers in Materials, 2024)
the application of edible coatings for preparing composite antibacterial spray coatings for fruit preservation by incorporating antibacterial nanoparticles has gained increasing attention. Chitosan (CS) is a natural polysaccharide used as an edible coating to preserve fruit, which can reduce water loss, enhance appearance, improve mechanical properties, etc. By combining with antibacterial material, it can reduce the microorganisms of fruit. Cerium (Ce) has excellent antibacterial activity, combined with the advantages of safety and low cost. Therefore, this contribution proposed a biocatalytic spraying coating for fruit preservation using CS composite metal-organic frameworks